The ins and outs of cholesterol in the vertebrate retina - Steven J. Fliesler; Lionel Bretillon (Journal of Lipid Research, 2010)
The vertebrate retina has multiple demands for utilization of cholesterol and must meet those demands either by synthesizing its own supply of cholesterol or by importing cholesterol from extraretinal sources, or both. Unlike the blood-brain barrier, the blood-retina barrier allows uptake of cholesterol from the circulation via a lipoprotein-based/receptor-mediated mechanism. Under normal conditions, cholesterol homeostasis is tightly regulated; also, cholesterol exists in the neural retina overwhelmingly in unesterified form, and sterol intermediates are present in minimal to negligible quantities. However, under certain pathological conditions, either due to an inborn error in cholesterol biosynthesis or as a consequence of exposure to selective inhibitors of enzymes in the cholesterol pathway, the ratio of sterol intermediates to cholesterol in the retina can rise dramatically and persist, in some cases resulting in progressive degeneration that significantly compromises the structure and function of the retina. Although the relative contributions of de novo synthesis versus extraretinal uptake are not yet known, herein we review what is known about these processes and the dynamics of cholesterol in the vertebrate retina and indicate some future avenues of research in this area.